Archival photo of a political rally - Mumbai Archive Project Team (Jio Institute, 2024)
A political rally passing outside Ramnath Keny’s home. This photo likely dates back to 1985, when the village still had mud roads. Today, a cemented pathway leads to his home amidst a landscape devoid of open spaces, marking a significant change.